Pelaksanaan Metode Tutor Sebaya dalam Materi Praktik Shalat Jenazah di MAN 2 Bantul - Wakhid Hasyim (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
Peers have a major influence on the development of a teenager. This influence occurs and visible impact on the daily behavior of a person. In addition to in everyday life, peer influence can also be felt in the learning process. One of the methods that use this approach is peer mentoring or commonly known as peer tutoring methods. This study was prepared to see the influence of peer mentoring or peer tutoring methods in learning Jurisprudence are still included in the subject cluster of Islamic Education for the funeral prayer practice material. Subjects in this study was the students of class X MAN 2 Bantul Mathematics 2 consists of 34 students. The treatment of the subject is done to a minimum. It aims to be able to see the natural method used is more focused on observation of the behavior of subjects and assessment of the results. The results of this study show that even with minimal treatment, peer tutoring method proved to have an influence on the successful education of students. It can be seen from the learning process more fluid, more active learners, relationships between friends in the learning process becomes warmer. Some of the obstacles posed serious concerns for learning is reduced. In addition, the closeness between friends looked dominant when there is no special treatment given to the learners. Learners prefer to be accompanied by a friend of the most familiar, is not considered the most capable in the subject matter.